Complications associated with intestinal infusion therapies in patients with Parkinson’s disease: a single-center retrospective study and 15-year experience - Igor Straka; Zuzana Andre; Zuzana Kosutzka; Karin Gmitterova; Karin Gmitterova; Milos Stevove; Zuzana Durkovicova; Radovan Juricek; Radovan Juricek; Peter Valkovic; Peter Valkovic; Michal Minar (Frontiers in Neurology)
IntroductionParkinson’s disease (PD) is a progressive neurodegenerative disorder, in advanced stages characterized by motor and non-motor fluctuations, significantly impacting patients’ quality of life (QoL). Advanced therapies, such as levodopa/carbidopa intestinal gel or carbidopa/levodopa enteral suspension (LCIG/CLES) and levodopa/entacapone/carbidopa intestinal gel (LECIG), offer continuous levodopa administration to reduce fluctuations and improve QoL. However, these therapies require invasive percutaneous endoscopic gastrostomy with jejunal extension (PEG-J), which can lead to complications. This study aimed to analyze the incidence of complications related to gastrojejunostomy in patients treated with LCIG/CLES or LECIG and their impact on therapy outcomes.MethodsThis retrospective study included PD patients treated with LCIG/CLES or LECIG at our center over 15 years. Patients were included if they had a PEG-J inserted and had been on LCIG/CLES or LECIG for at least 3 months. Complications were analyzed to identify trends and practical solutions for management.ResultsOf 111 PEG-J insertions, we analyzed 106 patients treated with LCIG/CLES or LECIG. A total of 77.4% experienced at least one adverse event (AE), predominantly device-related (69.8%). Common complications included knotting (24.4%), disconnection (22.8%), and occlusion (17.1%) of the inner tube. Serious AEs were rare but included three deaths within 30 days post-procedure, severe skin phlegmon in two patients, and severe gastrointestinal discomfort in one patient. The duration of PEG-J significantly correlated with AEs.ConclusionGastrojejunostomy-related AEs in LCIG/CLES and LECIG therapies are common but generally manageable with proper intervention. Serious complications are rare, with less than 10% discontinuing treatment due to dissatisfaction.